The contour effect: Differences in the aesthetic preference and stress response to photo-realistic living environments - Tawil, Nour; Ascone, Leonie; Kühn, Simone (Frontiers in Psychology, 2022)
The interest in the response to contours has recently re-emerged, with various studies suggesting a universal preference for curved over angular stimuli. Although no consensus has yet been reached on the reasons for this preference, similar effects have been proposed in interior environments. However, the scarcely available research primarily depends on schematic or unmatched stimuli and faces heterogeneity in the reported results. In a within-subject design, we investigated the curvature positive effect in photo-realistic indoor environments using stimulus material previously tested in virtual-reality (VR). 198 online participants rated 20 living room images, exclusively manipulated on the contour (angular vs. curved) and style (modern vs. classic) levels. The rating scales represented aesthetic (i.e., beauty, liking) and stress response (i.e., rest, stress). Beyond our main focus on contour, we additionally examined style and sex effects to account for potential interactions. Results revealed a significant main effect of contour on both aesthetic (η2g = 1-2%) and stress (η2g = 8-12%) response evaluations. As expected, images of curved contours scored higher than their angular counterparts on beauty, liking, and rest scales, and lower on the stress scale. In terms of interactions with style, curvature was aesthetically preferred over angularity only within images depicting modern style, however, its positive effect on stress response remained significant irrespective of style. Furthermore, we observed sex differences in aesthetic but not in stress responses, with curvature preference only found in women in our sample. In sum, our study primarily confirms positive effects of curvature, however, with multiple layers. First, the impact on aesthetic preference seems to be influenced by individual and contextual factors. Second, in terms of stress response, which might be especially relevant for designs intended to promote mental-health, the consistent effects suggest a more generalizable, potentially biophilic characteristic of curves. To the best of our knowledge, this is the first study to demonstrate these effects in fully-matched, photo-realistic, and multi-perspective living environment images. From the background of the previous VR trial whereby the same rooms did not elicit differences, our findings propose that static images vs. immersed presentations might yield different results in the response to contour.